Statistical Research on Braking Malfunctions of Passenger Rolling Stock in Operation - Juraj Gerlici; Alyona Lovska; Vasyl Ravlyuk; Yaroslav Derevianchuk; Oleksandr Derevyanchuk (Communications, 2025)
In this article are highlighted the results of the research on braking malfunctions of passenger rolling stock identified during the car maintenance. Based on the collected statistical material, the key factors that cause braking malfunctions in operation are highlighted. The main brake equipment units that account for the largest number of malfunctions in operation are determined. The data on the malfunctions of air distributors used in passenger rolling stock was systematized using the STATISTIKA software package. To ensure continuous monitoring and timely detection of defects in the brake system of passenger trains, it is critical to use modern diagnostic tools to predict the technical malfunctions of pneumatic and electropneumatic brake system units of passenger cars. Moreover, this would ensure compliance with the requirements for overhaul periods for passenger cars in accordance with the current standards and technical documents and would guarantee the traffic safety on Ukrainian railways.